Assessment of Arsenic Biosorption Kinetics of Isolated Indigenous Multi-Heavy Metal Tolerant Bacteria (Journal of Science and Technology Research, 2026)
The intrinsic properties of heavy metals, such as arsenic, chromium, and lead, as well as their widespread dispersion, make them a significant environmental hazard. Arsenic is specifically categorized as a carcinogen of group 1. Arsenic contaminated soil and water is hazardous because it penetrates into the food chain and causes health problems. The present study aimed to investigate the bioremediation potential of arsenicresistant bacteria. An exhaustive investigation was undertaken to isolate 26 bacterial strains exhibiting resistance to heavy metals. The ability of these isolated strains to assimilate arsenic from water solutions containing both As III and As V forms was then evaluated. Nineteen isolates demonstrated varying degrees of efficacy in the absorption of arsenic. Among these, the F1 isolate had shown the capability to uptake 30 μg/L As III and 32 μg/L As V The growth patterns of F1 indicated that the control group exhibited greater expansion than the group that received arsenic. Due to bioremediation potential of arsenic-resistant isolates, these isolates could help to bioremediate and restore As-contaminated environments. This research offers valuable insights into the mechanisms and kinetics of arsenic biosorption, thereby facilitating the advancement of environmental friendly and economically viable bioremediation approaches to mitigate arsenic pollution in soil and water.J. of Sci. and Tech. Res. 6(2): 143-150, 2025